ANALISI FINANSIAL USAHA PEMBENIHAN IKAN LELE DUMBO (Clarias gariepinus) DI KELURAHAN LEMBAH SARI KECAMATAN RUMBAI PESISIR KOTA PEKANBARU PROVINSI RIAU - Yulinda, Eni (Jurnal Perikanan dan Kelautan, 2012)
This research was conducted at Rumbai Pesisir (Lembah Sari), Pekanbaru,Riau Province on June 2009. The aimed of this research was to know the using ofproduction factors, the total cost of production, by the harvest and financialfeasibility of the hatchery of fresh water catfish. The research methode was surveymethode. Data were obtained by interviewing respondents based on questionersprovided and surveilance for 6 respondents (6 farmers).The result showed that the average production of capital was fiftyfivethousand fishes/harvest. The average of capital invested by the farmers was Rp12.740.923,33. The average of total cost was Rp 3.404.805/harvest, and theincome was Rp 5.150.000.harvest. The average of the farmer’s profit was Rp1.745.194/harvest.Based on the analysis of financial conducted by carculatiry RCR, ROI, andPPC, indicated that the business of hatchery of freshwater catfish by the farmer atRumbai Pesisir (Lembah Sari) is reasonable to be developed. Result of financialanalysis of RCR average is 1,55. ROI average is 55,81%/harvest and the value ofPPC average is 6,21. It means the financial capital will be paidback in six timesharvest.